Upaya Meningkatkan Pemahaman Sakramen Baptis dan Tobat Melalui Pembelajaran Berdiferensiasi Dengan Model PBL Pada Kelas VIII SMPN 2 Sebuku - Syem Dunia Yosep (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education in Indonesia faces various complex challenges. Therefore, efforts continue to be made by the government, educational institutions and society as a whole to improve access, quality and relevance of education in order to create a young generation that is skilled, competitive and ready to face global challenges. In the context of the Independent Curriculum, Catholic religious education in Indonesia focuses on developing religious understanding, moral values and Catholic spirituality for students. The independent curriculum emphasizes the Pancasila student profile. In this classroom action research, the researcher focuses on the dimension of independence which is based on the importance of forming strong character and mental attitudes in the younger generation, especially in facing complex global challenges. Experience often teaches us that what we know (knowledge in the cognitive realm) does not always make us successful in life. But our ability, tenacity and dexterity to digest and apply this knowledge in real life is what will make our lives more meaningful and of higher quality. This means we need to have a variety of intelligences for our lives to be successful. In fact, in a rather extreme way, Cooper and Sawaf (in Maman Sutarman, 2004: 4) in their research stated that intelligence in the cognitive domain (IQ) only contributes 4-10% to a person's life success. This means that 90% of a person's success in life is determined by their ability to digest and apply it in real life. Likewise, in religious life, people do not become saved because of the knowledge they have. People who believe are expected to be able to interpret and apply their faith in their daily lives. Therefore, Catholic religious education in schools should also enable students to have the competence to digest and apply knowledge of the faith in their daily lives. Education at school should provide maximum opportunities for every student to develop his or her potential. Education at school must also produce students who have the enthusiasm to continue learning throughout life (longlife education), full of curiosity and the desire to increase knowledge and skills that are useful for their lives. One of the keys to realizing such education is the existence of high and maintained motivation in students. However, the ideal learning atmosphere is as above; Students have high motivation to learn and it is not always possible to maintain it all the time. We hope that students can achieve optimal understanding and achievement, but what we encounter are students with low achievement and enthusiasm for learning. We hope that students will be actively involved in learning, but they are passive and less involved in the learning process so that their understanding is not optimal. We hope that students will develop into independent children, but every now and then we still encounter students who do not do the homework they are given. We experience situations like the above without exception in the Catholic religious education process.Based on the problem conditions above, teachers can provide learning experiences by designing the learning process. One learning model that can be applied is Problem Based Learning (PBL) or problem-based learning through differentiated learning strategies. The objectives of the research include (1) to find out how the Problem Based Learning model is used in increasing students' motivation and understanding of learning in the Sacrament of Baptism and Penance material in class VIII of SMP Negeri 2 Sebuku, (2) to find out the increase in learning motivation of students of VIII SMP Negeri 2 Sebuku with the help of the Problem Based Learning model through differentiated learning on the Sacrament of Baptism and Penance material, (3) to find out the use of the Problem Based Learning model through differentiated learning on the Sacrament of Baptism and Penance material, class VIII students at SMP Negeri 2 Sebuku can apply the student profile Pancasila dimension of mutual cooperation. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation and documentation. The data analysis technique used consists of data reduction by selecting raw data into information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results that refer to the problem formulation. The use of the Problem Based Learning model is in accordance with the syntax which includes orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting